Proses Asuhan Gizi Terstandar pada Pasien dengan Autoimun dan Sirosis Hepatis - Thalita, Kanasya; Muniroh, Lailatul (Universitas Batanghari Jambi, 2024)
Liver cirrhosis is a pathological condition of the liver that defines the end stage of hepatic fibrosis. Liver cell damage will lead to disruption of the liver structure and increased vascularization, causing enlargement of blood vessels in the gastric and esophageal areas. Liver cirrhosis is often caused by history of infection with hepatitis B virus or hepatitis C virus. Other causes include a family history of liver disease, excessive alcohol consumption, and a history of autoimmune disease. Providing a liver diet as one of the standardized Nutrition Care Process (NCP) for this disease aims to achieve and maintain optimal nutritional status without burdening liver function. The purpose of the case study is to find out the process of standardized nutritional care process for patients with autoimmune and liver cirrhosis through providing a liver diet. The case study was conducted in September 2023 at patients in Hospital X Surabaya. After monitoring and evaluation, the patient’s energy, protein, fat, and carbohydrates intake domains increased even though they had not yet reached the fulfillment target (<80%), the patient’s biochemistry domain was not received because the monitoring time was short, the patient’s physical/clinical condition continued to improve until the third day. The progress of the patient’s recovery over three days always increases. Starting with the stabilized appetite, the food intake received by patient increases so the patient’s physical and clinical condition continues to improve.